2018
DOI: 10.21608/ajs.2018.31665
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATING EFFECT OF PEPPER MINT OIL (Mentha pipreta) AND ITS NANO-FORMULATIONS ON SOME ENZYMATIC ACTIVITIES AND BIONOMICS OF COTTON LEAF WORM Spodoptera littoralis (BOISD.) [

Abstract: Different formulations of pepper mint oil, i.e. bulk, nano-emulsion and nano-encapsulation were evaluated against 2 nd and 4 th instar larvae of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Two percent of Tween 80 was added as an emulsifier. The formed emulsion was sonicated during 30 min using ultrasonic cleaner set, model WUC-DO3H 290W and 60 Hz, then sonicated for 1min using a high energy ultra sonication probe model VCX750, 750W, 20 kHz, and resonicated 30 min by the ultrasonic cleaner under cooling conditions using ice path according to Yousef, Dalia A. et al [17].…”
Section: Nano-emulsion Preparationmentioning
confidence: 99%
“…Two percent of Tween 80 was added as an emulsifier. The formed emulsion was sonicated during 30 min using ultrasonic cleaner set, model WUC-DO3H 290W and 60 Hz, then sonicated for 1min using a high energy ultra sonication probe model VCX750, 750W, 20 kHz, and resonicated 30 min by the ultrasonic cleaner under cooling conditions using ice path according to Yousef, Dalia A. et al [17].…”
Section: Nano-emulsion Preparationmentioning
confidence: 99%
“…In the same vein, Meriga et al (2012) The essential oil may impact insect development and metabolism (Moutassem et al, 2021). However, EOs causes reduced food ingestion (Roel et al, 2010), inhibits digestive enzymes (Yousef et al, 2018) and can result in prolongation of the development duration. Previously research showed that essential oil caused impaired feeding performance and inactivation of digestive (Bezzar-Bendjazia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nano-emulsions were created according to Youssef et al (2018) and Jerobin et al (2012). Essential oils were combined with distilled water (at a ratio of 1:2) after that Tween 80(2 percent) was added at a rate of 1 milliliter/liter.…”
Section: Nano Emulsions Of Plant Extractsmentioning
confidence: 99%